The relationship between the triglyceride-glucose index and lung function in healthy individuals: a cross-sectional study of 89,809 participants from Kangbuk Samsung health study - Hyun-Il Gil; Sungwon Lim; Min-Jung Kwon; Soo-Youn Ham; Jonghoo Lee; Jae-Uk Song (BMC Pulmonary Medicine)
Abstract Background The triglyceride-glucose index (TyG) has emerged as a reliable proxy for insulin resistance and metabolic dysfunction, showing associations with various health outcomes. While the relationship between metabolic health and respiratory function has been established, the association between TyG and lung function remains unclear, particularly in Asian populations. Therefore, we investigated whether TyG is associated with decreased lung function in a large sample of healthy Koreans. Methods We analyzed data from 89,809 healthy Korean adults (46,739 men, mean age: 38.5 years) who underwent health examinations in 2019, stratifying participants into quartiles based on their TyG index. Lung function impairment was defined using the lower limit of normal (LLN) derived from spirometric values at the fifth percentile of our population. We calculated adjusted odds ratios (aORs) and 95% confidence intervals (CIs) for lung function impairment, using the lowest TyG quartile as the reference group. Results Mean TyG index was 8.34 ± 0.57. Subjects in the highest TyG quartile exhibited the lowest predicted forced expiratory volume in one second (FEV1%) and forced vital capacity (FVC%) after adjusting for covariates (P < 0.001). Also, FEV1(L) /FVC(L) ratio significantly differ among the four quartiles (P < 0.001). Compared to the lowest quartile (Q1), the aORs with 95% CI for FEV1% below the LLN across increasing quartiles (Q2 to Q4) were 1.150 (1.002–1.320), 1.272 (1.103–1.466), and 1.535 (1.310–1.799), respectively. For FVC% below the LLN, aORs were 1.233 (1.065–1.428), 1.334 (1.159–1.536), and 1.745 (1.506–2.021), respectively. Both trends were statistically significant (all P for trend < 0.001). In contrast, the aORs for FEV1/FVC below the LLN showed no significant differences among groups (P for trend = 0.186). Conclusions We found a significant association between higher TyG index values and decreased lung function in a large sample of healthy Koreans. Longitudinal studies are needed to establish causality and explore the long-term implications of this relationship on respiratory health.